KONTEKS, KONTEKS, KONTEKS! ASPEK FUNDAMENTAL DALAM PROSES PENGOLAHAN ARSIP FOTO: Array - Adhie Gesit Pambudi (Jurnal Kearsipan, 2014)
Photograph archives are an important part in the collective memory which kept in archival institutions. These archives also have special format which arranged and described in another way than other forms of archives. The arrangement and description of photograph archives by functional context approach could increase the accessibility of users. This approach emphasized on main principles in archives management such as respect des fonds, provenance, and original order. The arrangement and description of photograph archives also is based on several international standards such as ISAD-G and Dublin Core Metadata Element Set. In the end, the access of photograph archives should be conducted via finding aids which correspond with the development of Information and Communication Technology so that users around the globe could easily access these archives.